조류와 장애물을 고려한 자율무인잠수정의 전역경로계획 - 이기영(Ki-Young Lee); 김수범(Subum Kim); 송창희(Chan-Hee Song) (Han-guk haeyang gonghak hoeji (Online), 2012)
This paper deals with the global path planning problem for AUVs (autonomous underwater vehicles) in a tidal current field. The previous researches in the field were unsuccessful at simultaneously addressing the two issues of obstacle avoidance and tidal current-based optimization. The use of a genetic algorithm is proposed in this paper to move past this limitation and solve both issues at once. Simulation results showed that the genetic algorithm could be applied to generate an optimal path in the field of a tidal current with multiple obstacles.